Solution of the Basic Boundary Value Problems for a Degenerate Elliptic Equation by the Method of Potentials - R.M. Askhatov; R.N. Abaydullin (Учёные записки Казанского университета: Серия Физико-математические науки)
Fundamental solutions to a degenerate elliptic equation are found. Using these fundamental solutions, simple and double layer potentials are built. The basic boundary value problems for a degenerate elliptic equation are reduced to the equivalent Fredholm integral equations of the second kind. Their solvability is proved.